The Spanish problem: report of speeches at the Plymouth Trades Union Congress 1936 - Bevin, Ernest, 1881-1951; Citrine, Walter, 1887-1983 (Trades Union Congress, 1936)
1936 018a-0007-018 292/946/18a/7(xviii)